Upgrading the shear strength of reinforced concrete corbels using strain hardening cementitious composites. (15th December 2022) - Hassan, Ali; Ellithy, Mohamed; El-Shafiey, Tarek F.
Highlights: Strain Hardening Cementitious Composites (SHCC) was used for strengthening RC corbels. The test parameters were; the thickness of the SHCC jacket, the jacket's reinforcement configuration and the partial/full jacketing. The use of the SHCC jacket increased the load-carrying capacity as well as the ductility of the strengthened corbels. A design model was proposed for the prediction of the shear capacity of the strengthened corbels. Abstract: This work aims to investigate the structural response of Reinforced Concrete (RC) corbels strengthened with Strain Hardening Cementitious Composites (SHCC) jackets. Ten specimens of double-sided corbels with a shear span-to-depth ratio (a/d) of 1.0 were constructed and tested. The test parameters included; (a) the thicknesses of the SHCC jackets which were 20, 30, and 40 mm, (b) the jacket's reinforcement configuration, three configurations were studied, namely, horizontal only, vertical only, and both vertical and horizontal, (c) the partial/full jacketing, when three corbels were partially strengthened with vertical SHCC stirrups of 30 mm thickness, these stirrups were applied at the middle of the shear span, the examined ratios were 33, 50 and 67 %. Based on the experimental findings, the SHCC strengthening has proved its capability to enhance the shear strength, cracking behaviour, and ductility of the tested corbels. In addition, providing internal steel reinforcement in the SHCC jackets improved the post-cracking performance of the tested corbels. In terms of the cost-to-value, based on the experimental outcomes, the minimum SHCC stirrup width ratio to have rather a similar efficiency to the full jacketing was 67 %. A shear strength model was proposed to predict the shear capacity of the fully jacketed corbels. The proposed model gave a good prediction for the shear capacity with sufficient accuracy when compared with the experimental results.